PENERAPAN METODE DEMONSTRASI DENGAN MEDIA AUDIO VISUAL UNTUK MENINGKATKAN MOTIVASI BELAJAR DAN HASIL BELAJAR PENGETAHUAN DASAR TEKNIK MESIN SISWA KELAS X SMK MUHAMMADIYAH PRAMBANAN TAHUN AJARAN 2021/2022 - rio andrian; samidjo samidjo; dianna ratnawati (Program Studi Pendidikan Vokasional Teknik Mesin, Universitas Sarjanawiyata Tamansiswa, 2023)
This research sought to increase learning motivation and learning outcomes of basic knowledge of mechanical engineering (PDTM) class X SMK Muhammadiyah Prambanan Machining through the application of demonstration methods with audio visual media can improve. This research is a type of classroom action research consisting of 3 cycles, each cycle consisting of four stages starting from the stages of planning, implementation, observation, and reflection. The subjects in this study were students of class X Mechanical Engineering. Data collection techniques used observation sheets, multiple choice tests and documentation. The data analysis technique used quantitative descriptive analysis techniques. The results showed that the use of the demonstration method with audio-visual media can increase the motivation and learning outcomes of PDTM students of class X Mechanical Engineering. learning motivation has increased can be seen from the results of the average value in the first cycle of 66.38% in the high category, increased in the second cycle to 70.13% with the high category, and increased in the third cycle to 77.38% in the high category. In the first cycle of students who reached the KKM of 42.86% students had achieved the standard minimum score of 75, increased in the second cycle to 57.14% and in the third cycle increased to 78.57%.